PENGARUH KESADARAN WAJIB PAJAK, PENGETAHUAN PAJAK, DAN SANKSI PAJAK TERHADAP KEPATUHAN WAJIB PAJAK PELAKU UMKM KARAWANG TAHUN 2023 - Sutopo, Rahmawan; Safitry, Martina (Institut Ilmu Sosial dan Manajemen STIAMI, 2025)
Regional Original Revenue (PAD) is one of the primary sources of funding for regional development. In the effort to optimize PAD, the Micro, Small, and Medium Enterprises (MSMEs) sector plays a significant role as regional taxpayers. However, the tax compliance level of MSMEs in Karawang Regency still faces various challenges, such as low taxpayer awareness, inadequate tax knowledge, and suboptimal implementation of tax penalties. This study aims to analyze the influence of taxpayer awareness, tax knowledge, and tax penalties on the Regional Original Revenue (PAD) of Karawang Regency. This research employs a quantitative approach with a causal research design to identify the cause-and-effect relationships between variables. Primary data were collected through questionnaires distributed to 100 MSMEs in Karawang Regency selected using a purposive sampling method, while secondary data were obtained from official government reports. The results of the study indicate that taxpayer awareness, tax knowledge, and tax penalties have a positive and significant influence on Regional Original Revenue, both partially and simultaneously. Tax knowledge has the greatest influence, followed by taxpayer awareness and tax penalties. This study provides practical implications for the Karawang Regency government to strengthen tax awareness programs, enhance access to tax information, and ensure effective enforcement of tax penalties. Through an integrated approach, the potential of PAD from the MSME sector can be optimized sustainably.